Translating humor in animated short films: Humorous verbal elements in English and Finnish versions of five Bugs Bunny cartoons - Voitto, Eetu (My University, 2017)
This thesis covers the translation of verbal humorous elements in five animated short films from English into Finnish. The analyzed films were originally released theatrically in the United States in the 1940s and 1950s. The films are part of the series Looney Tunes and Merrie Melodies and feature the character Bugs Bunny, known in Finnish as Väiski Vemmelsääri. The films have been released on the DVD Looney Tunes: Väiski Vemmelsäären parhaat. Two distinct Finnish translations of each film have been included on the disc: a dubbed version and a subtitled version. In addition to comparing the translated versions with the original versions of the films, the two distinct translations have been compared with each other. In doing this, the different conventions of dubbing and subtitling, along with the differences between spoken and written text, have been considered. The films contain both verbal and visual humor, as well as combinations of the two types. The thesis focuses on verbal humor due to it constituting the majority of the translations, although visual humor will also be considered when it functions along with the verbal humor, or significantly affects the translation thereof. Of the different types of humorous elements found in the films, the most represented have been described in their own sections: cultural references, puns and wordplay and speech patterns. Various examples from both the original English versions of the films and their Finnish translations have been included, the latter having been back-translated into English to assist comparisons. There are multiple differences between the target audiences in the source and target culture. In addition to the different country and era, the two audiences notably differ in age demographics. These differences have also been noted in the thesis, and their effects on the translations have been considered. The primary criterion, based on which the different versions of the films have been compared, is the transferring of the original films' humorousness to the target culture. The theoretical framework of the analysis consists of the skopos theory, Christiane Nord's function-plus-loyalty model and Patrick Zabalbeascoa's classification of humorous elements from an audiovisual translation point of view. In addition, a new classification of humorous elements in the Bugs Bunny cartoons based on their prevalence and notability has been created for the purposes of the thesis. In conclusion, it will be determined which of the two translations is more successful at achieving its targeted function. In addition, both translations will be further assessed for their respective benefits and drawbacks.